Speech by the Honourable Chief Minister, Penang at the Dinner by the State Government on the occasion of the Official Visit to the Honourable Prime Minister, Malaysia, to Penang, to be held at the Rasa Sayang Hotel, Penang, on Saturday 9th October 1976 at 8.00 p.m. - Lim, Chong Eu (1976)
On behalf of the State Government of Penang, I take great pleasure in extending a very warm welcome to our Hon’ble Prime Minister, and Yang Berbahagia Datin Suhaila to the State of Penang.